Improving alliance satisfaction: the resource alignment of IT competency in small healthcare centers - Lin, Chad; Huang, Y.; Jalleh, Geoffrey (Academic Global Publications, 2008)
Title: Improving Alliance Satisfaction: The Resource Alignment of IT Competency in Small Healthcare CentersKeywords: e-health, IT competency, alliance performance, health promotion.Category of paper: Research paperPurpose of the research/paper: The objective of this research is to establish whether greater deployment of resource alignments leads to more satisfactory alliance. Two research questions are proposed: (1) do organizations which use supplementarity alignment more likely to be satisfied with their alliance activities compared with those which have adopted asymmetric supplementarity alignment? and (2) do organizations which use complementarity alignment more likely to be satisfied with their alliance activities compared with those which have adopted asymmetric complementarity alignment? Methodology: Case Study Interviews. Findings: IT competency can be built into four types of IT resource alignment for cooperative alliance and different types of IT resource alignment can affect alliance performance differently. Moreover, we found that the contribution of symmetric complementary and supplementary IT competency by both the focal and partner firms had a significant positive impact on the degree of satisfaction of the focal firms.Value of the paper: The paper will be of interest to academics, health professionals, and healthcare managers. Number of pages: 16 Number of tables/figures: 4 Section headings: Abstract, Introduction, Literature review, Research methodology, Research findings, Discussions, Managerial Implications, Limitation, conclusions, and future directions, References.